2006 International Conference on Nanoscience and Nanotechnology 2006
DOI: 10.1109/iconn.2006.340543
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed PECVD for the Growth of Silicon Nanowires

Abstract: Silicon nanowires of high density and high aspect ratio similar to those shown in the literature [1, 2] have been grown using a variation of Plasma Enhanced Chemical Vapour Deposition (PECVD) known as Pulsed Plasma Enhanced Chemical Vapour Deposition (PPECVD) using a range of different modulation frequencies. For the range of frequencies used it was found that the presence of a modulated silane plasma increases the average density and sample coverage of silicon nanowires. Both of these effects are proposed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…From Figure 1b it can be seen that the conductive ITO coated materials, both Corning glass and Asahi ITO produce nanowires at a higher density than the uncoated corning glass of similar thickness. Previous work using PPECVD has indicated that part of the increase in density with using a 1kHz pulsed plasma is due to the induced heating in the substrate 3 . By introducing a conductive layer to the surface of the otherwise insulating glass substrate before the deposition of the gold catalyst layer this effect could be enhanced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From Figure 1b it can be seen that the conductive ITO coated materials, both Corning glass and Asahi ITO produce nanowires at a higher density than the uncoated corning glass of similar thickness. Previous work using PPECVD has indicated that part of the increase in density with using a 1kHz pulsed plasma is due to the induced heating in the substrate 3 . By introducing a conductive layer to the surface of the otherwise insulating glass substrate before the deposition of the gold catalyst layer this effect could be enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…A further modification of PECVD uses a square wave signal to produce Pulsed PECVD (PPECVD). We have previously shown 3 that the use of PPECVD improves nanowire density and overall sample coverage in comparison to PECVD. Silicon nanowires have been produced using a variety of substrates, although most interest is devoted to what is being grown, the substrate used can affect the ultimate usefulness of the silicon nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…PECVD has been improved to pulsed PECVD (PPECVD) which uses modulated plasma to support the deposition process. Parlevliet and Cornish [34,35] group have shown that PPECVD technique could be produced Si nanowires at higher area density more than normal PECVD. The PPECVD grows Si nanowires using metal catalysts like Al, Ag, Cu, Au, Sn and In.…”
Section: Catalyst-assisted Growth Technologiesmentioning
confidence: 99%
“…The PPECVD grows Si nanowires using metal catalysts like Al, Ag, Cu, Au, Sn and In. According to the results of Parlevliet and Cornish [34,35] group, the Ag was the best effective catalysts under conditions of growth temperatures, and also Ag catalysts could be produced Si nanowires with substrate coverage of seven to eight times greater than the other catalysts.…”
Section: Catalyst-assisted Growth Technologiesmentioning
confidence: 99%
“…A modification of PECVD is pulsed PECVD which uses a modulated plasma to aid the deposition process. We have previously shown [3] that PPECVD can be used to produce silicon nanowires with a greater area density than conventional PECVD. In the VLS mechanism the role of the catalyst is to encourage the growth of single crystal silicon nanowires.…”
Section: Introductionmentioning
confidence: 99%